Supervisi Akademik dalam Mendukung Pembelajaran Berdiferensiasi pada Implementasi Kurikulum Merdeka: A Systematic Literature Review - Siti Futukhatul Khikmah; Inmanora Inmanora; Korinna Al Emira; Mohamad Muspawi; Eva Iryani; Denny Denmar (CV. Global Cendekia Inti, 2026)
This study aims to analyze the challenges of supervisory management in overseeing differentiated learning within the implementation of the Merdeka Curriculum. The study employs a systematic literature review (SLR) approach, referring to the PRISMA guidelines to ensure a systematic, transparent, and replicable literature selection process. Data were analyzed from 20 scientific articles selected based on inclusion and exclusion criteria across various academic databases. The findings indicate that the implementation of the Merdeka Curriculum promotes a transformation in the learning paradigm toward a student-centered approach, with differentiated learning as the core of pedagogical practice. However, its implementation still faces several challenges, particularly gaps in teachers’ competencies, limited infrastructure, and suboptimal understanding of the concept of differentiated instruction. In this context, academic supervision plays a strategic role as a mechanism for strengthening teachers’ capacity. Nevertheless, current practices tend to be administrative in nature and are not yet oriented toward instructional improvement. This study highlights the importance of reorienting academic supervision toward a more adaptive, collaborative, and coaching-based approach to effectively support the implementation of differentiated learning. These findings contribute to the development of a supervision model that is more aligned with the demands of the Merdeka Curriculum.